The Impact of Customary Law Implementation in Crime Resolution after the Reform of National Criminal Law in Indonesia - Hasman Hidayah; T. Riza Zarzani; Fitri Rafianti (PT. Sinergi Legal Publisher, 2025)
This study examines the impact of the application of customary law in resolving crimes in Aceh Province following the enactment of the National Criminal Code (KUHP) Number 1 of 2023. As the only region with special autonomy in the legal sector, Aceh has a dual legal system that integrates national law, Islamic law, and customary law through Qanun. This study examines how the recognition of customary law in the new KUHP strengthens the legitimacy of resolving minor criminal cases in Aceh, which have previously been resolved through customary village deliberation mechanisms. Through a normative and sociological approach, this study found that the provisions in Article 2 paragraph (1) and Article 97 of the 2023 Criminal Code explicitly recognize existing laws within society as sources of criminal law, including customary laws codified through regional regulations such as the Aceh Qanun. Empirical findings indicate that more than 60% of minor criminal cases in several districts in Aceh have been resolved through customary institutions, with a high level of community acceptance and satisfaction. This emphasizes the role of customary law as an effective and contextual means of restorative justice. However, implementation challenges such as disharmony between the Criminal Code and Qanun (Indonesian Law), suboptimal understanding among law enforcement officials, and limited customary documentation are significant concerns. Therefore, steps are needed to synchronize regulations, increase the capacity of customary institutions, and foster cross-sectoral development so that customary law can function optimally within a pluralistic national criminal justice system.